Pharmaceuticals biodegradation by activated sludge and pure cultures - Bessa, Vânia S. (2013)
The occurrence of pharmaceuticals in the environment have been a topic of increasing concern. Most of the pharmaceuticals are not completely mineralized in the human body and are released on the sewage systems as the pharmaceutical itself and as their “biologically active” metabolites through excretion, as well as by improper elimination and disposal. Once current wastewater treatment plants (WWTPs) are not designed to remove these emerging pollutant, they are easily released into the environment.The effects of halogen on biological properties of molecules have had a marked impact on various fields such as pharmacology. It can improve metabolic stability, bioavailability and interactions with the biological target. However, it also increases the recalcitrance of the molecule to biotic and abiotic degradation. Ciprofloxacin (CPF) and Diclofenac (DCF) are two widely used halogenated pharmaceuticals, commonly found in the environment in concentrations that can range ng L−1 to mg L−1. CPF is a common human and veterinary broad-spectrum fluoroquinolone antibiotic. DCF is a non-steroidal anti-inflammatory drug (NSAID), also used as analgesic and antithermic treatment. In the present study, biodegradation of CPF and DCF was assessed by selective enrichements with actived sludge and with pure cultures of three different strains - Labrys portucalensis (F11) and two Rhodococcus spp. (FP1 and S2) – which had previously demonstrated capacity to degrade a range of halogenated compounds. For CPF selective enrichments, a degradation of 100% was achived after 206 days, although without fluoride release. These findings indicate that these selective enrichments are good candidates to find a bacterial strain able to biodegrade CPF. Regarding the pure cultures, F11 exhibited the highest degradation capacity (57%) after 62 days, but also without fluoride release. Concerning DCF selective enrichments, it was released 68% of the stoichiometrically expected cloride ion behind 131 days. In the experiments with pure cultures, F11 and S2, was released the totality of the stoichiometrically expected cloride, elapsed 131 days. These results indicate that these two strains are promising for DCF biodegradation.